تقويم كتب التاريخ للمرحلة الثانوية في ضوء معايير الجودة الشاملة من وجهة نظر المعلمين - العدوان، زيد سليمان محمد (جامعة الإسكندرية - كلية التربية, 2015)
هدفت الدراسة إلى تقويم كتب التاريخ للمرحلة الثانوية في ضوء معايير الجودة الشاملة من وجهة نظر المعلمين، وتقصي أثر متغيرات الجنس، والمؤهل العلمي، وسنوات الخبرة في تقديرات المعلمين لجودة كتب التاريخ للمرحلة الثانوية في الأردن. ولتحقيق ذلك اتبعت الدراسة المنهج الوصفي التحليلي، حيث تم تصميم استبانة مكونة من (55) فقرة، بعد التحقق من صدقها وثباتها، وتم توزيعها على عينة الدراسة المكونة من (203) معلمين ومعلمات يدرسون مادة التاريخ للمرحلة الثانوية في مديرات التربية والتعليم لإقليم الوسط للعام الدراسي 2014/2015. وأظهرت نتائج الدراسة توافر معايير الجودة الشاملة في كتب التاريخ للمرحلة الثانوية بدرجة متوسطة، وعدم وجود فروق ذات دلالة إحصائية بين تقديرات المعلمين لجودة كتب التاريخ للمرحلة الثانوية تعزي إلى متغير الجنس، باستثناء معيار مصادر التعلم، والمعايير الفنية والإخراج وذلك لصالح تقديرات الإناث، وعدم وجود فروق ذات دلالة إحصائية في تقديرات المعلمين لجودة كتب التاريخ للمرحلة الثانوية تعزي إلى متغير سنوات الخبرة، باستثناء معيار مصادر التعلم، ومعيار التقويم وذلك لصالح المعلمين ذوي الخبرة العالية (10 سنوات فأكثر)، وعدم وجود فروق ذات دلالة إحصائية تعزي إلى متغير المؤهل العلمي، باستثناء معيار الأنشطة وقضايا البحث، ومعيار التقويم وذلك لصالح المعلمين ذوي المؤهل العلمي (دراسات عليا)، وفي ضوء نتائج الدراسة قدم الباحث مجموعة من التوصيات.
The present study aimed to evaluate the history textbooks of the secondary stage in the light of the total quality standards from the teachers' viewpoint, and to investigate the effect of the variables (gender, qualification, and years of experience) in the teachers’ evaluation of the quality of these textbooks of the secondary stage in Jordan. To achieve that, the study has followed the analytical descriptive methods designing a questionnaire which consisted of (55) items. After confirming its validity and stability, it was distributed to the study sample which consisted of (203) male and female teachers of the history subject of the secondary stage in the Directorates of Education of the Middle District for the scholastic year 2014-2015. The findings of the present study showed that the availability of the total quality standards in the history textbooks for the secondary stage at a medium degree, and the absence of statistically indicative differences between the teachers' evaluation of the history textbooks of the secondary stage attributed to gender variable, except for the learning resources standard, the technical standards and editing in favor of the females estimations. The findings also showed the absence of statistically indicative differences between the teachers' evaluation of the history textbooks of the secondary stage attributed to the variable of years of experience except for the learning resources standard and the evaluation standard in favor of the teachers with long experience (10 years and more). Moreover, the findings showed the absence of differences with statistically significance attributed to the scientific qualification except for the activities standard, the research issue and evaluation standards in favor of the teachers with scientific qualification (graduate studies).In the light of the study's findings, the researcher presented a group of recommendations
Keywords: التعليم الثانوي -- المناهج الدراسية -- كتب التاريخ -- الجودة الشاملة